2016
DOI: 10.1039/c5ra21533a
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of metal-binding proteins by a newly discovered OsmY homolog in Cupriavidus metallidurans for the biogenic synthesis of metal nanoparticles

Abstract: A newly discovered OsmY protein homolog of Cupriavidus metallidurans for use in protein secretion and biogenic synthesis of nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The Cu chaperone protein, CupC, was used for further analysis, as this was the only protein to contain a metal binding domain that could be responsible for binding Au-complexes. 18 A model of the Cu chaperon protein was constructed based on two related Cu-binding proteins: a 'multispecies' copper chaperone, heavy metal binding (modular protein) of an organism described solely as Cupriavidus (WP_00864966) which had a 100% homology between amino acids 68-133 with the Cu chaperon protein identified in this study, and a copper chaperone from Cupriavidus sp. BIS7 (WP_019451883); the resulting protein model is shown in Fig.…”
Section: Identification Of Au-binding Proteinsmentioning
confidence: 97%
See 2 more Smart Citations
“…The Cu chaperone protein, CupC, was used for further analysis, as this was the only protein to contain a metal binding domain that could be responsible for binding Au-complexes. 18 A model of the Cu chaperon protein was constructed based on two related Cu-binding proteins: a 'multispecies' copper chaperone, heavy metal binding (modular protein) of an organism described solely as Cupriavidus (WP_00864966) which had a 100% homology between amino acids 68-133 with the Cu chaperon protein identified in this study, and a copper chaperone from Cupriavidus sp. BIS7 (WP_019451883); the resulting protein model is shown in Fig.…”
Section: Identification Of Au-binding Proteinsmentioning
confidence: 97%
“…However, the presence of Cu(I)-binding sites demonstrates that the protein CupC contains metal-binding sites that are suitable for Au(I)-binding, due to chemical similarity Au complexes are predicted to bind to Cu-binding sites. 4 In addition, a study by Ouyang et al, 18 showed that Au nanoparticles were formed in the presence of truncated CupC fused to the secretion carrier Rmet_3428, suggesting the binding of Au to a metal-binding motif in CupC. Overall, this highlights the limitations of computer-based protein modelling, which relies on the utilisation of suitable datasets that is not available for the Au-complex studied.…”
Section: Identification Of Au-binding Proteinsmentioning
confidence: 98%
See 1 more Smart Citation